Standard specification for Pressure Vessel Plates, Alloy Steel, High-Strength, Quenched and Tempered (American Society of Testing Materials, 2006)
This specification2 covers high-strength quenched and tempered alloy steel plates intended for use in fusion welded boilers and other pressure vessels.